Haemocompatibility and ion exchange capability of nanocellulose polypyrrole membranes intended for blood purification - Ferraz, Natalia (The Royal Society, 2012)
Composites of nanocellulose and the conductive polymer polypyrrole (PPy) are presented as candidates for a new generation of haemodialysis membranes. The composites may combine active ion exchange with passive ultrafiltration, and the large surface area (about 80 m2 g−1) could potentially provide compact dialysers. Herein, the haemocompatibility of the novel membranes and the feasibility of effectively removing small uraemic toxins by potential-controlled ion exchange were studied. The thrombogenic properties of the composites were improved by applying a stable heparin coating. In terms of platelet adhesion and thrombin generation, the composites were comparable with haemocompatible polymer polysulphone, and regarding complement activation, the composites were more biocompatible than commercially available membranes. It was possible to extract phosphate and oxalate ions from solutions with physiological pH and the same tonicity as that of the blood. The exchange capacity of the materials was found to be 600 ± 26 and 706 ± 31 μmol g−1 in a 0.1 M solution (pH 7.4) and in an isotonic solution of phosphate, respectively. The corresponding values with oxalate were 523 ± 5 in a 0.1 M solution (pH 7.4) and 610 ± 1 μmol g−1 in an isotonic solution. The heparinized PPy–cellulose composite is consequently a promising haemodialysis material, with respect to both potential-controlled extraction of small uraemic toxins and haemocompatibility.